Impacts of a changing environment on marginal coral reefs in the Tropical Southwestern Atlantic. (1st September 2021) - Soares, Marcelo Oliveira; Rossi, Sergio; Gurgel, Anne Rebouças; Lucas, Caroline Costa; Tavares, Tallita Cruz Lopes; Diniz, Beatriz; Feitosa, Caroline Vieira; Rabelo, Emanuelle Fontenele; Pereira, Pedro Henrique Cipresso; Kikuchi, Ruy Kenji Papa de; Leão, Zelinda M.A.N.; Cruz, Igor Cristino Silva; et al.
Abstract: The peculiar shallow-water reefs of the Tropical Southwestern Atlantic Ocean have thrived in conditions considered suboptimal (e.g., moderate turbidity, higher level of nutrients, and resuspension of sediments) under the optics of classical coral reefs. Recently, these marginal reefs have been hypothesized to provide climate-change refugia from natural and anthropogenic impacts; yet with little empirical evidence. Therefore, in this article we discuss the known effects of multiple pressures on the Brazilian reefs. A wide evaluation of the peer reviewed literature reported that bleaching events affected 26 species of scleractinians, hydrocorals, octocorals, and zoanthids in turbid-zone reefs over the last 26 years (1994–2020) in the Tropical SW Atlantic Brazil. Between 1994 and 2018 no species suffered post-bleaching mass mortality. However, the recent and intense heatwaves of 2019 and 2020 caused higher mortality rates in several key foundation corals (e.g., Millepora alcicornis, Millepora braziliensis, and Mussismilia harttii ) showing that the SW Atlantic reefs are not long-term protected and universal refuges. Moreover, other direct and indirect human pressures threaten these tropical reefs. Local and regional (e.g., pollution and fisheries) and large-scale pressures (e.g., global warming and marine heatwaves) act simultaneously on the health of these reefs, which intensifies negative species-specific impacts. We outline the occurrence of pressures that have been important factors responsible for the reduction in species richness and reef fish biomass, changing geo-ecological functions, altered reef composition and dominant morpho-functional groups, as well as phase shifts. Along with large-scale climatic changes, such as heatwaves, fisheries, urbanization, mining disasters, oil spills, increased sedimentation, increased warming, marine debris, contamination by domestic, agricultural, and industrial effluents, and introduction of invasive species are likely the most severe pressures on Brazilian reefs. We discuss that the "Brazilian reef refuge hypothesis" could be partially applied for some stress-tolerant massive corals during acute disturbances (short-term refuge); yet should not be assumed as a reef ecosystem-wide feature under ongoing environmental change. Therefore, we argue that it is essential to alleviate the main local and regional human impacts and to adopt resilient-based management strategies at local and global scales to protect the low-functional redundancy and higher endemism of these unique marginal coral reefs. Graphical abstract: Image 1 Highlights: Bleaching events affected 26 reef species over the last 26 years. The most reef-building corals did not exhibit post-bleaching mass mortality before 2019. Occurrence of multiple human pressures are responsible for the decline of Brazilian reefs. These marginal coral reefs are not long-term and universal refuges.